2020
DOI: 10.4102/jsava.v91i0.2052
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance patterns of Pseudomonas aeruginosa isolated from canine clinical cases at a veterinary academic hospital in South Africa

Abstract: Although Pseudomonas aeruginosa (P. aeruginosa) can infect both animals and humans, there is a paucity of veterinary studies on antimicrobial resistance of P. aeruginosa in South Africa. Secondary data of canine clinical cases presented at the hospital from January 2007 to December 2013 was used. The following information was recorded: type of sample, the date of sampling and the antimicrobial susceptibility results. Frequencies, proportions and their 95% confidence intervals were calculated for all the catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
6
10
1
Order By: Relevance
“…In this study, MDR prevalence (39.53%) of P. aeruginosa strains was found to be similar to the MDR prevalence of the studies reported by Dos Santos In these studies, sulphonamide, tetracycline, fluoroquinolone and aminoglycoside group antibiotics, which are known to exhibit intrinsic resistance in P. aeruginosa, were found at high levels in MDR profile combinations (Turkyilmaz 2008;Eliasi et al 2020). In addition, the ability of P. aeruginosa to develop acquired resistance also contributes to the formation of MDR (Pang et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, MDR prevalence (39.53%) of P. aeruginosa strains was found to be similar to the MDR prevalence of the studies reported by Dos Santos In these studies, sulphonamide, tetracycline, fluoroquinolone and aminoglycoside group antibiotics, which are known to exhibit intrinsic resistance in P. aeruginosa, were found at high levels in MDR profile combinations (Turkyilmaz 2008;Eliasi et al 2020). In addition, the ability of P. aeruginosa to develop acquired resistance also contributes to the formation of MDR (Pang et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study indicated that Pseudomonas was highly penicillin-resistant; likewise, Eliasi et al (2020) reported that it was highly resistant to amoxicillin-clavulanic acid (92.0%). Interestingly, the results of our study indicated that Pseudomonas could lead to imipenem resistance, which is consistent with the findings of Eliasi et al (2020). Additionally, Klebsiella species were found to be resistant Vet Integr Sci Vet Integr Sci Chawnan et al Vet Integr Sci.…”
Section: Discussionmentioning
confidence: 51%
“…The bata-lactamase intrinsic resistance pathway of Pseudomonas has arisen as a result of low membrane permeability and AmpC beta-lactamase production (Pechère and Köhler, 1999). The findings of this study indicated that Pseudomonas was highly penicillin-resistant; likewise, Eliasi et al (2020) reported that it was highly resistant to amoxicillin-clavulanic acid (92.0%). Interestingly, the results of our study indicated that Pseudomonas could lead to imipenem resistance, which is consistent with the findings of Eliasi et al (2020).…”
Section: Discussionmentioning
confidence: 68%
“…In this sense, P. aeruginosa and S. choleraesuis show the lowest susceptibility to non-fractioned extract because their growth was inhibited at concentrations above 1400 µg/mL. Additionally, the formation of compact biofilm could conferrer them a major resistance that protects them from the antibacterial properties of the extract [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%